MIDDLE PLEISTOCENE SMALL MAMMAL FAUNA OF THE CAVE LOCALITY AT VINYAVY (L'VIV REGION) - Popova, L.; Krochak, M.; Krokhmal', O.; Tzyzh, E. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
A new locality of the Pleistocene small mammals at Vynyavy (L'viv region) has been discovered in the filling of rock shelters beneath the massive well-cemented sandstone of the Opillia Suite of the Badenian, the Middle Neogene. The locality was formed as a result of pellet accumulation. Predators, whose activity was forming the taphocoenosis, were birds and predatory beasts that inhabited the rock shelters and small caves in the looser underlying sandstone. The fauna includes fossils of insectivores, lagomorphs and rodents. ThepresenceofArvicolachosaricusand the evolutionarylevelofotherarvicolidsallowidentification this fauna as Khasarian one. The closest analogue of Vynyavy, with respect to the geological age, is a fauna from sub-moraine deposits of the Dnieper area, Matviivka. Ecologically, Vynyavy fauna shows similarity with Medzhybizh (Syngilian fauna of the Bug area). Geological age of the locality is the Middle Pleistocene, Dnieprovian climatolith, and, taking into account ecological features of the fauna, most likely, its beginning. On the basis of small mammal fauna, open steppe habitats should be reconstructed for thе tіme span presented by Vynyavy fauna. Climate was colder than the present one, although not extremely cold, which is evidenced by the presence of insectivores. Climate was also wet enough, as soon as all xerophillous species are absent. Special characteristic feature is the absence of Laguridae, usual for the Pleistocene of Ukrainian group. Arctic component is presented by a lemming. High percentage of the water vole in the taphocoenosis indicates extensive areas of flood-plains and high fluvial activity, which could be expected during interstadials rather than during cold epochs. Otherwise, a decrease of seasonal floods would have resulted in foresting of valley and, as a consequence, in the appearance of forest mammal species, which are observed in Vinyavy fauna. Remains of ground squirrels belong to Spermophilusodessanus, a fact that supports a recent (Holocene) colonization of this area by its present inhabitant, S. citellus.
Keywords: Middle Pleistocene; small mammal fauna; voles; evolutionary level; palaeoecology